The Art of Metaphor Translation: Taylor Swift's 'Willow' in Indonesian - Sumarga, Sresthi; Putri, Astari Amalia (Journal of Language, Literature and Teaching, 2024)
This research aims to help listeners understand the meaning of the lyrics of "Willow" by Taylor Swift through metaphor translation strategies from English to Indonesian. The challenges faced include the numerous figurative meanings that are difficult to translate literally, necessitating metaphor translation strategies to convey the emotional nuances contained in the lyrics. The research method used is qualitative descriptive, involving the collection and recording of data from the lyrics of "Willow." The results indicate that among the five metaphor translation strategies proposed by Larson (1984), there are several strategies that are most suitable for use, particularly translating metaphors into similes. This aims to ensure that the emotional message and the deep meaning implied in the song can be effectively conveyed to Indonesian listeners.Keywords: translation strategy of metaphors, figurative meaning, song lyrics, Taylor Swift, translation, emotional nuances.